Changing trend in mode of delivery in pregnant women with human immunodeficiency virus (HIV) in a teaching hospital in the UK. (16th November 2010) - Venkitaraman, U; Navti, O; Nakade, M; Kalathy, V; Jethwa, M; Boon, L; Qualie, J; Howarth, E; Dhar, J; Khare, M
Abstract : Introduction: Increasing trend towards vaginal delivery in the presence of an undetectable viral load in pregnant women with HIV has been reported in the literature.1 Method: The authors reviewed the mode of delivery in women with HIV over a nine year period in our hospital. Result: The mode of delivery was vaginal delivery in 81 of 189 pregnancies (43%) and caesarean section in 108 pregnancies (57%). Vaginal delivery is advised when there are no obstetric contraindications and the viral load is undetectable. Where vaginal delivery is contemplated, care is taken in labour to minimise the risk of mother to child transmission (MTCT). In our study in the absence of obstetric indications and in the presence of an undetectable viral load the intended mode of delivery was vaginal delivery in thirteen out of twenty two pregnancies (59%) in the period 2000–2004 and in sixtyfive out of eighty nine pregnancies (73%) in the period 2005–2008. This increase in the uptake of the vaginal delivery option is a reflection of the antenatal counselling these patients received regarding mode of delivery and the impact of a multidisciplinary approach to their management. MTCT rates in our study was 1.56%. Conclusion: Over the last 9 years there has been an increase in the number of vaginal deliveries to HIV positive women in our unit with no significant increase in MTCT of HIV.